Meninjau Kembali Komitmen Indonesia dalam Paris Agreement 2015 Era Presiden Joko Widodo (Energi Baru Terbarukan) - Ibnu Al Hasyim; Afief Azmi; Muhammad Zulfikar (Fakultas Ilmu Sosial dan Ilmu Politik - Universitas Garut, 2024)
Environmental issues and climate change due to greenhouse gas emissions from burning fossil fuels have become global challenges that necessitate the search for sustainable solutions. The use of non-renewable energy such as petroleum, natural gas, and coal as the main practice worldwide has resulted in significant negative impacts on the environment such as pollution, environmental degradation, and habitat destruction. Therefore, the transition to New Renewable Energy (NRE) that utilizes renewable resources such as solar, wind, water, and biomass is an important solution that is more environmentally friendly and sustainable. Indonesia, as a country with significant greenhouse gas emissions, has a responsibility to contribute to climate change mitigation efforts in accordance with the 2015 Paris Agreement. During Jokowi's presidency, the Indonesian government showed a strong commitment to achieve emission reduction targets by developing renewable energy. This research analyzes and evaluates the policy and implementation of EBT in Indonesia through a qualitative approach and policy analysis. By examining the government's specific actions in implementing the Paris Agreement and the Energy Law, this research aims to understand the efforts, challenges, and recommendations to support a sustainable energy transition in Indonesia.